2007
DOI: 10.1007/s10143-007-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential stabilization with ghost screwing after posterior resection of spinal metastases via transpedicular route

Abstract: Various surgical methods have been described for treating spinal metastases, namely, en bloc spondylectomy, minimally invasive techniques, and anterior and posterior approaches. The main goals in surgical intervention for these lesions are tumor removal and establishment of strong, durable stabilization. The least invasive method is always preferred. Posterior transpedicular spondylectomy meets all these needs, as this method achieves tumor excision and stabilization of the anterior and posterior spine through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…There were 3 prospective cohort trials 32,33,38 and 11 retrospective case series. 4,5,[8][9][10]12,13,18,20,30,34 Class I evidence reporting on the use of PTAs was not available from any of the selected articles.…”
Section: Transpedicular Corpectomymentioning
confidence: 99%
See 4 more Smart Citations
“…There were 3 prospective cohort trials 32,33,38 and 11 retrospective case series. 4,5,[8][9][10]12,13,18,20,30,34 Class I evidence reporting on the use of PTAs was not available from any of the selected articles.…”
Section: Transpedicular Corpectomymentioning
confidence: 99%
“…Bilsky et al 18 (8 patients) evaluated single-stage PTA for circumferential epidural decompression and 3-column stabilization using a titanium cage for upper thoracic spine neoplastic disease and reported one neurological outcome (I/M Frankel grades 100%). Senel et al 30 (7 patients) evaluated circumferential stabilization with ghost screwing (that is, the creation of an acrylic anterior graft that is directly connected to the posterior transpedicular stabilizing system via 2 ghost screws) after posterior resection of spinal metastases via a transpedicular route. They reported that neurological function remained unchanged for all patients not lost to follow-up.…”
Section: Transpedicular Corpectomymentioning
confidence: 99%
See 3 more Smart Citations